A influência de diferentes fatores estruturais do habitat nas assembleias de peixes em recifes costeiros da Paraíba, nordeste brasileiro - Araújo, Antônio Limeira Felinto de (2021)
Coastal reefs are threatened worldwide by constant habitat loss, causing a decline in the inhabiting populations, consequently changing community structure. Fish are organisms that respond quickly to these impacts. Therefore, understanding the ecological role of species in these ecosystems is essential for their conservation, especially concerning fish interaction with reef structure. This study was conducted in three parts, addressing the following questions: (1) How are fish assemblages distributed in reefs with different levels of structural habitat complexity, and what factors influence the richness, abundance and trophic groups in these environments? (2) What is the relationship between microhabitat and fish activities in different zones of a coastal reef? (3) Are there variations in the diversity and habitat use among fish species between patches and continuous reefs within the same reef system? Samples were carried out on coastal reefs in northeastern Brazil, between the municipalities of Cabedelo and João Pessoa, in the Paraíba State. Visual underwater census and active search methods were carried out by a single observer, using free diving, to record fish species and assess environmental characteristics. Random transects and the timed swim method were used. The results showed that fish are influenced by several factors, such as substrate type, live cover, presence of shelters, and rugosity, both in areas with different levels of complexity and among different reef zones and between continuous and patch reefs. These factors, which characterize each habitat type, are strongly related to community structure, shaping the spatial distribution pattern of species. High-complexity reefs had four times more individuals compared low-complexity reefs, but there was a considerable record of species in common between these environments. The composition and species diversity varied among different reef zones, as well as the use of microhabitats by the fish. Reef patches and continuous reefs showed variations in fish species diversity, despite low variation in benthic composition in these environments. It can be observed that variations in the physical structure of the habitat play a determining role in the distribution of fish assemblages, indicating patterns of species richness, abundance, and diversity in the studied reef environments. Therefore, it is understood that heterogeneous environments are essential for the maintenance of reef fishes, as connectivity between habitats with different structural characteristics is crucial. This connectivity ensures greater efficiency in activities such as foraging, reproduction, and species protection, as well as providing greater resilience to reef environments through the energy flow.